A Microworld Simulator for Process Control Research and Training. (September 2013) - Dyre, Brian P.; Adamic, Eric J.; Werner, Steffen; Lew, Roger; Gertman, David I.; Boring, Ronald L.
We introduce and will demonstrate a new software tool for creating simulations of simplified process control tasks—what Vincente (2000) termed microworlds— for research and training applications. This tool builds on previous software tools, such as the synthetic task environment DURESS, but provides more flexibility in simulation design, a more realistic physics model, and additional components for representing complex processes, such as auditory and visual alarms for nuclear power plants. Further, our microworld simulation tool can be used for a variety of tasks, from flexibly specifying a synthetic environment for research on a desktop computer to scaling up to large format touch displays with realistic controls typical of high-fidelity process control simulators. Potential applications of the microworld simulator include research on the cognitive engineering of human-machine interfaces used in process control, training of process control operators and other personnel, and rapid prototyping and testing of process controls and displays.